Love in the time of cholera - García Márquez, Gabriel, 1927-2014 (Penguin Books, 1989)
The story of a fantastic wedding, the return of the bride to her parents in disgrace, her brothers' resolve to seek revenge on her corruptor, and the townspeoples' refusal to depart from routine.